Role of social factors, self-efficacy and technological support on the use of virtual learning environment among teachers - Noor Lela Ahmad; Rusliza Yahaya; Hariyaty Ab Wahid; Nadhirah Syafiqah Mohd Fazil (Institute of Advanced Engineering and Science, 2023)
Virtual learning environment (VLE) has been introduced in educational institutions such as schools, colleges, and universities to encourage a systematic online teaching and learning platform. This paper aims to examine the effect of social factors, self-efficacy, and technological support on the utilization of VLE in the educational process. A quantitative approach was employed and the data was collected through a set of questionnaires administered to selected respondents. A total of 356 accounting teachers from secondary schools in Peninsular Malaysia were chosen as the samples. A reflective measurement model in partial least square-structural equation modeling was utilized to measure the effect of the exogenous latent variable on the endogenous latent variable. Results indicated that social factors namely (colleagues, administrators, and school culture) significantly affect the use of VLE among teachers. Further, self-efficacy and technological support namely (facilities quality, internet access, and technical support) positively influence teachers to apply VLE during teaching. The quality of technological facilities in schools needs to be developed to promote effective educational processes and motivate teachers to use digital technology. Further, it is strongly suggested that teachers need to be given appropriate training and ongoing support to develop their skills in using digital technology.